Parallel evolution of microstructure, physical properties and their relationships in Co₀.₅Zn₀.₅Fe₂O₄ ceramics - Muhamad Zulkimi, Muhammad Misbah (2013)
For more than eight past decades, the ferrite research literature has only very superficially dealt with the question of how the evolving microstructure of a ferrite material relates to its accompanying, resultant magnetic properties. The literature has only covered in great detail the answers for the case of ferrite materials obtained from final sintering. Thus, this work is a fresh attempt to critically track the evolution of magnetic properties parallel to the microstructural changes in bulk Co0.5Zn0.5Fe2O4 samples and to relate the properties to the changes wherever possible. In this study, high energy ball milling (HEBM) was used to prepare Co0.5Zn0.5Fe2O4 nanoparticles with sintering temperatures from 500 oC to 1350 oC and with a 50 oC increment. Physical characteristics of the as-prepared and sintered samples were studied using X-ray diffraction (XRD), scanning transmission electron microscopy (STEM) and Field Emission Scanning Electron Microscope (FESEM); characterization of magnetic properties was carried out by using An Agilent Model 4291B impedance/material analyser in the frequency range of 1 MHz to 1.0 GHz which was used to measure the permeability and the loss factor. The magnetic properties of the samples were investigated using a MATS-2010SD Static Hysteresisgraph. The XRD results confirm that Cobalt zinc ferrite cannot be formed directly through milling alone, but heat treatment is necessary. After sintering at 550 oC, the cobalt zinc ferrite phase was obtained earliest at this temperature with an average grain size in the nanometric range (0.089μm). The microstructure studies of Co0.5Zn0.5Fe2O4 showed that the grain size increased, density was increased and porosity was decreased as the sintering temperature increased. The parallel evolution of hysteresis parameters with microstructural properties for sintered samples was studied. The saturation induction, Bs, increased with the enhancement grain size. The highest saturation induction value for sintered samples is 1486.00 G. The coercivity value was increased with increasing grain size and reached a maximum value (24.93 Oe) before dropping with further increasing grain size. The permeability and loss factor values were observed and can be classified into three different groups with the utilization the similar B-H hysteresis loop results: weak ferromagnetic (first group), moderate magnetic (second group) and strong ferromagnetic (third group) behavior. The resistivity value of the sample under investigation had semiconductor behavior. The Curie temperature varied slightly for the samples due to stoichiometric changes allocated with zinc loss. Finally, after analysing the results and the observations of the work mentioned above, it is strongly believed that there are three factors found to sensitively influence the samples content of ordered magnetism –their ferrite-phase crystallinity degree, the number of grains above the critical grain size and large enough grains for domain wall accomodation. This research work has shed new light on the microstructure-magnetic properties evolution in ferrites.